2023
DOI: 10.1111/odi.14574
|View full text |Cite
|
Sign up to set email alerts
|

Salivary and serum levels of neutrophil proteases in periodontitis and rheumatoid arthritis

Abstract: ObjectiveThe aim was to profile serum and salivary levels of active‐matrix metalloproteinase (aMMP)‐8, tissue inhibitor MMP (TIMP)‐1, aMMP‐8/TIMP‐1 ratio, total MMP (tMMP)‐9, tMMP‐9/TIMP‐1 ratio, myeloperoxidase (MPO), and human neutrophil elastase (HNE) in periodontitis and rheumatoid arthritis (RA).Materials and MethodsRheumatoid arthritis patients with periodontitis (RA + P, n = 26), periodontally healthy RA patients (RA, n = 23), systemically healthy periodontitis patients (P, n = 24), and controls (C, n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…The included studies represent 6 cross-sectional, [ 20 , 22 , 23 , 25 , 26 , 33 ] 2 prospective interventional [ 21 , 24 ] and 1 prospective cohort study. [ 19 ] The features of the selected studies are shown in Supplementary Table S1, http://links.lww.com/MD/K117 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The included studies represent 6 cross-sectional, [ 20 , 22 , 23 , 25 , 26 , 33 ] 2 prospective interventional [ 21 , 24 ] and 1 prospective cohort study. [ 19 ] The features of the selected studies are shown in Supplementary Table S1, http://links.lww.com/MD/K117 .…”
Section: Resultsmentioning
confidence: 99%
“…Kirchner, Jäger, Krohn-Grimberghe, Patschan, Kottmann, Schmalz, Mausberg, Haak, Ziebolz [23] * * * ** * 6 Dogukan Yilmaz, katariina Niskanen, Emel Gonullu, Taina Tervahartiala, Ulvi kahraman Gursoy, Timo Sorsa [33] * * * * * * 6 For instance, the diagnosis of PD in the literature varied; some studies defined PD as "mild/moderate/severe," [20][21][22][23]25] while others used clinical parameters such as clinical attachment level, probing depth and bleeding on probing [19,24,26] to define periodontal disease. None of the included studies categorized PD into chronic and aggressive types.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The study by Yilmaz et al [41] showed that only serum levels of MPO were significantly elevated in patients with RA compared with the healthy controls, regardless of periodontal status. In turn, salivary MPO concentrations were increased but without statistical significance.…”
Section: Autoimmunological Disordersmentioning
confidence: 97%